Biochemical Composition and Nutritive Value of Common Fish Feeds Available in Cochin Area - P.G., Viswanathan Nair; O., Kavitha; R., Anandan; Mathew, suseela (Fishery Technology, 2025)
The biochemical composition of some of the feeds used in aquaculture is reported. Four grower feeds and 19 other locally available feeds were used for the study. Moisture content varied from 6.3-12.4%; and protein content from 22.4 to 46.9% and mineral content varied from 5.3 to 24.2%. Some of the feeds wee found to be very low in fat content (1%). Variations in the proportions of the amino acids in the grower feeds were to a limited extent only. But fatty acid analysis showed great variation among the grower feeds. C1SJ) was not detected in two of the samples. Detectable amount of Cjg.3 was not present in any of the samples analyzed. The level of was very low in one of the samples and the same feed was with low level of (1.7%). The study points out the need for formulating the fish feed on the basis of the nutritional requirements of fish.